Effective Organization of Extracurricular Activities in Azerbaijan Schools and Near and Far-Abroad Countries - B. Ismayilova (Открытое образование (Москва), 2021)
Introduction. The main task of secondary schools is to prepare a new generation for activity, develop the creative potential of an individual, educate a creatively thinking younger generation, possessing the entire set of intellectual and cultural qualities. In this regard, the correct organization of extracurricular activities is of great importance. The aim of this article is to analyze the experience of conducting extracurricular activities in Azerbaijan schools and near and farabroad countries. Research methodology and methods. In 2019 a pedagogical experiment was conducted among 219 pupils of urban, regional and rural schools in Azerbaijan. Initially, a preliminary survey was conducted among pupils of IV, VI, VIII, X, XI grades and a few months later a second survey was conducted among 453 pupils with the question "In what direction do you prefer to work in extracurricular activities?". A survey was used as a research method. Results and discussion. The international experience of carrying out extracurricular activities is described. Proposals were put forward for the effective organization of extracurricular activities in accordance with the requirements of the XXI century. Azerbaijan experience in organizing extracurricular activities is described. In the process of the pedagogical experiment, in extracurricular activities, the pupils tried to improve their skills in various areas, using educational computer games, role-playing games and developing simple educational games. During the experiment, we found that pupils from different grades voluntarily joined the extracurricular activities. A second survey was conducted among pupils and the results show that they were more interested in educational games and computer setting operations. Conclusion. Research results show that the correct organization of extracurricular activities has a significant impact on the intellectual development of pupils, contributes to the achievement of good learning outcomes in the educational process at school. In connection with the relevance of this topic, theoretical and practical research related to various forms of extracurricular activities and solving problems of their organization and implementation will be continued.